The implications of warmer winters for ice climbing: A case study of the Mount Washington Valley, New Hampshire, USA - Voorhis, Jimmy; McDowell, Graham; Burakowski, Elizabeth; Luneau, Taylor (Frontiers in Human Dynamics, 2023)
Ice climbing is important to the culture and economies of mountain communities worldwide. However, warming winters call into question the future of livelihoods associated with ice climbing. In response, this study presents a case study of observed and simulated ice climbing conditions in the Mount Washington Valley of New Hampshire, USA, as well as local climbing guide’s experiences of and responses to these changes. First, variability in ice conditions were evaluated by classifying and summarizing ice characteristics depicted in a 20-year collection of conditions reports (n = 372) including photos and written observations for a benchmark ice climb (Standard Route). Next, climate model ensembles were used to simulate probable changes in future ice season lengths according to intermediate and high climate forcing scenarios (i.e., RCP 4.5 & RCP 8.5). Finally, a survey and focus group were conducted with Mount Washington Valley ice climbing guides to examine observations and lived experiences of warming winters. The study reveals significant effects of climate change for current and projected ice climbing conditions as well as marked, and often differentiated, vulnerability and adaptability to these changes amongst climbing guides. The study provides the first formal assessment of the implications of warming winters for ice climbing guides, and uses a unique mixed-methods approach applicable in other locales where climate change is impacting ice climbing activities and associated livelihoods.